Metode Pembelajaran Hadits Menurut Adnan Hasan Al-Baharits - Kurniawati, Ani; Basuki, Basuki (Lembaga Yasin AlSys, 2023)
The teaching and learning process which is an interaction carried out by all components of learning. All components of learning have different functions, so learning will be imperfect and difficult to achieve the expected goals. One that needs to be maximized is a learning method that is in accordance with the learning material and expected goals. In research using this literature method, it examines the learning methods used by Adnan Hasan Baharits in learning Hadith. This is important to study to know how effective ways to study Hadith. This research produces three main points, namely: first, before doing learning, teachers should prepare to explore the material to be taught by reading other references so that when delivering the material is not only fixated on one reference. Second, the ongoing learning process should involve all components of learning, especially students by providing opportunities for students to argue and think critically so that the learning process is not only teacher-oriented. Third, that learning evaluation can be done by giving questions to students related to the material that has been taught or by giving assignments to be done at home.